Prevalence of splenomegaly and factors contributing to splenomegaly among pancytopenia patients: a facility-based cross-sectional study - N., Kaushik; S., Basanth Kumar; R., Vedavathi (International Journal of Research in Medical Sciences, 2023)
Background: The spleen is an organ that cannot be clinically felt in a normal individual. Splenomegaly is a significant diagnostic indicator of the presence of underlying pathology. It is associated with a number of diseases like hematological, infectious, portal hypertension and immunological problems. However, it’s unclear what exactly causes hypersplenism. The objective was to assess the prevalence of splenomegaly in people with pancytopenia and the contributing factors. Methods: A cross-sectional study was conducted among adult patients diagnosed with pancytopenia in a tertiary care hospital in Bengaluru, Karnataka. We have considered only inpatients who accessed care at the facility over a period of 12 months from Aug 2021 to July 2022 among those who have given written informed consent. Socio-demographic details, smoking status, alcohol consumption history, existing comorbidities, and other biological parameters were assessed by accessing the medical records. The abdominal ultrasound of the admitted patients was used to diagnose splenomegaly. Results: Splenomegaly was present in 25 (56.8%) of patients out of 44 we enrolled. Among those patients, 17 (38.6%) had mild, while 4 (9.1%) had moderate and massive splenomegaly respectively. The majority were females (28 versus 16 males) and the mean age was 44.84 years (±15.45 SD). The age ranges from 24-80 years. We observed that patients aged 36-50 years and comorbidities like hypertension and hypothyroidism were the associated factors for splenomegaly. Conclusions: The prevalence of splenomegaly among pancytopenia patients is high. This is a significant clinical indication that requires careful investigation. Ageing, hypertension, and hypothyroidism are contributory factors for splenomegaly in patients with pancytopenia.